Synthesis, spectroscopic studies and antibacterial activity of new lauroyl thiourea amino acid derivatives - Abdul Kadir, Maisara; Ramli, Rozana; Mohd Yusof , Mohd Sukeri; Ismail, Naemah; Ngah, Nurziana (India, 2016)
Four new thiourea compounds have been successfully synthesized and characterized from combination of lauroyl chloride, ammonium thiocyanate and simple amino acids in acetone. The structure of the respective compounds, namely 3-(3-dodecanoyl-thioureido)propionic acid (R1), 2-(3-dodecanoyl-thioureido)-3-methyl butyric acid (R2), (3-dodecanoyl-thioureido)acetic acid (R3) and 2-(3-dodecanoyl- thioureido)-3-phenyl propionic acid (R4) are confirmed by combination of spectroscopic techniques such as infrared, ultraviolet and nuclear magnetic resonance. The antibacterial activity of these compounds are investigated towards selected bacteria and the results show that compound R4 displays better antibacterial activity compared to R1-R3 and as well as to few reported compounds. Compound R4 shows good antibacterial activity towards two Gram-negative bacteria Escherichia coli and Salmonella typhimurium, with inhibition zone approximately 8 mm wide and minimum inhibitory concentration (MIC) 50 μg/mL, respectively. The good results given by R4 might be attributed by the presence of alkyl and phenyl group that increases the lipophilicity and stability of the compounds.